Gentrifizierung in periurbanen Räumen Frankreichs – am Beispiel des Umlandes von Nancy - Marchal, Hervé; Stébé, Jean-Marc; Weber, Florian (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
The process of gentrification in the peri-urban districts of French cities has scarcely been touched upon in recent research, which has hitherto seen the phenomenon as typically associated with core urban areas. The tendency has been to view the periphery through the lens of the social crisis of the banlieues. In contrast, the present article focuses on gentrification in the metropolitan area of Nancy (Grand Est region) as a development that also plays a role in municipalities around major cities and especially around regional metropolitan centres. Starting with a survey of current research approaches, the article first pinpoints some gaps and methodological imbalances that need to be tackled, before embarking on the case study of peri-urban Nancy. Statistical data and empirical surveys in the form of qualitative interviews indicate how Nancy's peri-urban districts have developed a logic of separation, exclusion and social decoupling – typical features of gentrification – particularly in connection with the construction of new single-family houses as a supplement to existing residential stock. Key questions here concern individual motives for choosing a particular residential location, and the creeping "segregation from above" that accompanies this process. The image of France's peri-urban spaces that arises from this study stands in explicit contrast to the received, markedly negative connotations of the "urban periphery".
Keywords: Peri-urban spaces; peri-urban gentrification; heterogenization; metropolitan area of Nancy (Lorraine); qualitative approach